Optimizing Fluency Training for Speaking Skills Transfer: Comparing the Effects of Blocked and Interleaved Task Repetition. Issue 2 (24th September 2020) - Suzuki, Yuichi
Abstract: In an exploration of the effects of task‐repetition practice on fluency development, English‐as‐a‐foreign language learners performed three oral narrative tasks involving six‐frame cartoons for 3 consecutive days. They engaged in task‐repetition practice under either a blocked (Day 1: A‐A‐A; Day 2: B‐B‐B; Day 3: C‐C‐C) or an interleaved (Day 1: A‐B‐C; Day 2: A‐B‐C; Day 3: A‐B‐C) task repetition schedule. The results yielded by a posttest involving new six‐frame cartoons indicated that blocked practice resulted in greater fluency development (faster articulation rate and shorter mid‐clause pause duration) than did interleaved practice. Moreover, the learners in the blocked‐practice group tended to pause more frequently at clause boundaries. Blocked practice also led to significantly longer mean length of run and higher phonation/time ratio during training, although this advantage failed to transfer to meaningful pretest–posttest changes. These dynamic fluency developmental patterns are discussed to elucidate the underlying proceduralization in L2 speech processes. Abstract :